2015
DOI: 10.1142/s1793984415400073
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Synthesis of Cy5-Encapsulated Photostable Fluorescent Silica Nanoparticles for Bioimaging

Abstract: A new type of Cy5-encapsulated photostable fluorescent silica nanoparticles (FSNPs) bearing positive charges have been successfully fabricated by a reverse microemulsion synthesis in one-pot. The Cy5 dye containing four primary amines are embedded into silica via covalent bonds through a silane coupling agent (GPTMS), followed by co-condensation with tetraethylorthosilicate. The uniform-sized, spherical and monodispersed FSNPs have high fluorescence intensity and photostability. The FSNPs exhibit high stabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…More importantly, it has been reported that incorporation of cyanine dyes into silica nanoparticles could tremendously improve the photo-stability and brightness of cyanine dyes [23]. In search of cyanine dye-doped silica nanoparticles, to the best of our knowledge, there are only few reports on the success of encapsulating cyanine dyes inside silica nanoparticles [24][25][26][27][28][29][30][31][32]. Within these reports, either more stable dyes [24,26,28,30,31] or biomaterials [29] were used to assistant the formation of fluorescent silica nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More importantly, it has been reported that incorporation of cyanine dyes into silica nanoparticles could tremendously improve the photo-stability and brightness of cyanine dyes [23]. In search of cyanine dye-doped silica nanoparticles, to the best of our knowledge, there are only few reports on the success of encapsulating cyanine dyes inside silica nanoparticles [24][25][26][27][28][29][30][31][32]. Within these reports, either more stable dyes [24,26,28,30,31] or biomaterials [29] were used to assistant the formation of fluorescent silica nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…In search of cyanine dye-doped silica nanoparticles, to the best of our knowledge, there are only few reports on the success of encapsulating cyanine dyes inside silica nanoparticles [24][25][26][27][28][29][30][31][32]. Within these reports, either more stable dyes [24,26,28,30,31] or biomaterials [29] were used to assistant the formation of fluorescent silica nanoparticles. However, commercially available cyanine dyes are very challenging to be incorporated into silica nanoparticles, mainly because these dyes cannot tolerant the alkaline condition used in silica nanoparticle formation [24,27].…”
Section: Introductionmentioning
confidence: 99%
“…During sol-gel synthesis, hydrolysis and polycondensation of alkoxysilanes occur, forming solid nanoparticles, which will grow around the surface of the micelles [ 30 ]. The W/O system is suitable for the fixation of polar components inside the silica particle [ 31 ] while the oil-in-water (O/W) emulsion is desirable for nonpolar substances [ 32 ]. Nonpolar molecules immobilization is possible due to the hydrophobic effect using the silica matrix modified with phenyl fragments [ 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%